1985
DOI: 10.3109/00365528509089284
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms in Patients with Peptic Ulcer and Hematemesis and/or Melena Related to the Use of Non-Steroid Anti-Inflammatory Drugs

Abstract: One hundred and seven consecutive patients with hematemesis and/or melena and a diagnosis of duodenal, gastric, or esophageal ulcers were interviewed immediately before or after endoscopy about the use of non-steroid anti-inflammatory drugs (NSAIDs) and symptoms before the hemorrhage. If the patients admitted no symptoms of abdominal pain or discomfort, nausea, vomiting, or heartburn, they were classified as having no ulcer symptoms before the hemorrhage. Patients who had not taken NSAIDs during the last 48 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…The lack of correlation between subjective symptoms and endoscopically observed mucosal lesion scores is in agreement with other contemporary reports (7,10,23) and with the clinical observation that serious GI haemorrhage due to an NSAID may occur without prior symptoms (12). This rather disturbing phenomenon may indicate that subjective symptoms reported by patients are a rather unreliable indicator of severe side effects of NSAIDs.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The lack of correlation between subjective symptoms and endoscopically observed mucosal lesion scores is in agreement with other contemporary reports (7,10,23) and with the clinical observation that serious GI haemorrhage due to an NSAID may occur without prior symptoms (12). This rather disturbing phenomenon may indicate that subjective symptoms reported by patients are a rather unreliable indicator of severe side effects of NSAIDs.…”
Section: Discussionsupporting
confidence: 78%
“…Subjective gastrointestinal side effects are a poor indicator of possible complications of NSAID therapy (12). We therefore wanted to optimize the evaluation of G T effects of NSAIDs, emphasizing the comparison of endoscopic assessment and faecal blood loss and their possible relation to reported symptoms.…”
mentioning
confidence: 99%
“…The association between NSAID and silent peptic ulcer has been studied for long time, but still remains in debate. The majority of the literature supported the role of NSAID in developing silent peptic ulcer by masking ulcer pain [13][14][15][16]. However, these findings were almost all derived by univariate analyses without adjusting confounding factors such as age and sex.…”
Section: Discussionmentioning
confidence: 83%
“…The exact cause of the obscure manifestations of these GI pathologies in DM remains unclear. An overall hyposensitivity due to visceral neuropathy, altered central processing to visceral stimulation, and frequent antiplatelet use in diabetic patients has been suggested (5,28,29). Recent studies further demonstrated a reduced density and abnormal morphology of gastric mucosal nerve fibers in both type 1 and type 2 diabetic subjects (30,31).…”
Section: Discussionmentioning
confidence: 99%